Sociodemographic Predictors of Anal Cancer Screening and Follow-up in Human Immunodeficiency Virus–Infected Individuals. Issue 5 (September 2018) - Wells, Jessica S.; Holstad, Marcia M.; Watkins Bruner, Deborah
Abstract : Background: Anal cancer in the United States is generally rare; however, human immunodeficiency virus (HIV)–infected individuals are 28 times more likely to be given a diagnosis of anal cancer than the general population. Objective: The aim of this study was to examine the rates and sociodemographic predictors of anal cancer screening and follow-up anoscopy in a sample of HIV-infected individuals. Methods: Data for this study (n = 200) were derived from a retrospective chart review of randomly selected HIV-infected individuals. Data analyses included Pearson's correlation coefficient statistic to examine bivariate associations and logistic regression modeling for prediction of anal Papanicolaou test screening and follow-up anoscopy. Results: Screening rates and follow-up after an abnormal anal Pap test were low. Women were less likely to be screened for anal cancer (odds ratio [OR], 0.244; P = .007). Men who have sex with men were almost 4 times more likely to be screened for anal cancer (OR, 3.7; P = .02). Men who have sex with men were 6 times more likely to have follow-up after an abnormal anal Pap test compared with heterosexual men or women of any sexual orientation (OR, 6.88; P = .002). Conclusions: High-risk groups for anal cancer should be targeted for preventative measures as part of a cancer prevention plan to decrease the personal and clinical burden associated with anal cancer. Implications for Practice: Cancer prevention is a multistep process that requires screening and follow-up efforts, where healthcare providers play a vital role in these efforts. Findings from this study can inform strategies to improve screening and follow-up rates in HIV-infected individuals.